2023
DOI: 10.1187/cbe.22-07-0148
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Practices in Education: A Primer for Practitioners

Abstract: This essay serves as an introduction for practitioners to reflective practices in education. Benefits, methods for engaging in reflective practices and potential challenges are highlighted with further resources outlined in the supplemental materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
2
6
0
1
Order By: Relevance
“…Teacher G also pointed out her appreciation for utilizing feedback with students since it helped them with learning: "Feedback is of great importance in fixing errors and confirming correct information". Reflective practices are frequently discussed in terms of their benefits for students, but the advantages they offer to educators are often overlooked in the literature [23]. This study has filled the gap and revealed significant advantages of reflective practices for teachers.…”
Section: Cspd Effective Pedagogymentioning
confidence: 91%
See 1 more Smart Citation
“…Teacher G also pointed out her appreciation for utilizing feedback with students since it helped them with learning: "Feedback is of great importance in fixing errors and confirming correct information". Reflective practices are frequently discussed in terms of their benefits for students, but the advantages they offer to educators are often overlooked in the literature [23]. This study has filled the gap and revealed significant advantages of reflective practices for teachers.…”
Section: Cspd Effective Pedagogymentioning
confidence: 91%
“…Despite the global recognition of the significance of reflective writing, a significant concern among in-service teachers in many developing countries is the limited exposure to systematic reflective models that facilitate enhanced reflexivity [22]. The literature points out the need to consider practitioners' potential misunderstandings regarding reflection by PD facilitators [23]. Therefore, Gibbs' reflective model, which is widely used for educational purposes [24], serves as a structured framework to assist teachers in their reflective writing process [22].…”
Section: Effective Professional Development In Csmentioning
confidence: 99%
“…Reflection is essential to understand the situation that happened in the past, present, and future. According to Machost and Stains [22], 'In less philosophical phrasing, reflection entails considering past or present experiences, learning from the outcomes observed, and planning how to better approach similar situations in the future.' In this research, reflection was used to evaluate student's expression of patriotism in the present situation.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…Formative and summative assessments are powerful tools for collecting data on student learning during a lesson. Educators can use these data to evaluate the effectiveness of the instructional sequence, reflect on changes that would foster student learning, and take actions that strengthen the lesson activities . Educators should use these data to critically reflect on aspects of the lesson that they can modify to enhance student learning.…”
Section: Educational Frameworkmentioning
confidence: 99%